Recent advances in understanding and managing resistant/refractory hypertension [version 1; peer review: 2 approved] - Michael Doumas; Konstantinos P Imprialos; Manolis S Kallistratos; Athanasios J Manolis (F1000Research, 2020)
The management of resistant hypertension presents several challenges in everyday clinical practice. During the past few years, several studies have been performed to identify efficient and safe pharmacological and non-pharmacological options for the management of such patients. The Spironolactone versus placebo, bisoprolol, and doxazosin to determine the optimal treatment for drug-resistant hypertension (PATHWAY-2) trial demonstrated significant benefits with the use of spinorolactone as a fourth-line drug for the treatment of resistant hypertension over doxazosin and bisoprolol. In addition, recent data support that spironolactone may demonstrate superiority over central acting drugs in such patients, as well. Based on the European guidelines, spironolactone is recommended as the fourth-line drug option, followed by amiloride, other diuretics, doxazosin, bisoprolol or clonidine.  Among several device-based approaches, renal sympathetic denervation had fallen into hibernation after the disappointing results of the Renal Denervation in Patients With Uncontrolled Hypertension (SYMPLICITY HTN) 3 trial. However, the technique re-emerged at the epicenter of the clinical and research interest after the favorable results of three sham-controlled studies, which facilitated novel catheters and techniques to perform the denervation. Significant results of iliac anastomosis on blood pressure levels have also been demonstrated. Nevertheless, the technique-related adverse events resulted in withdrawal of this interventional approach. Last, the sympatholytic properties of the carotid baroreceptor activation therapy were associated with significant blood pressure reductions in patients with resistant hypertension, which need to be verified in larger controlled trials. Currently device-based approaches are recommended only in the setting of clinical trials until more safety and efficacy data become available.